Umbilical cord blood nucleated red cell count as a marker of perinatal asphyxia - Chavan, Manisha; Patil, Pratibha M.; Bagali, Vijay (International Journal of Contemporary Pediatrics, 2018)
Background: Nucleated RBCs are a common observation in the circulating blood of newborn. Number of nRBC in cord blood and perinatal asphyxia shows good correlation. Perinatal asphyxia ranks as the second most important cause of neonatal death after infections accounting for about 30% mortality worldwide. Objective of the present study was designed to find the relation between umbilical cord blood nRBC count and perinatal asphyxia. Methods: The present one-year prospective case control study was carried out. A total of 100 babies divided into two groups of 50 each as cases and controls. Term babies with perinatal asphyxia were enrolled as cases and term babies without perinatal asphyxia born during same period were included as control. Results: The distribution of cord blood pH in cases showed maximum babies (80%) with pH value of <7 and 38% of the children were detected to have HIE stage II followed by 26% with stage I and 4% with stage III. At admission, 48 hours and 72 hours, significantly higher number of babies were found to have higher cord blood nRBC count (p<0.001) and the mean cord blood nRBC count was found to be significantly high at all the intervals (p <0.001). Comparison of mean cord blood nRBC count among cases in stage III was significantly high compared to stage II and I (p<0.001) at admission, 48 hours and 72 hours. Conclusions: Cord blood nRBC can be used as surrogate marker for asphyxia. The clearance of nRBC from the circulation may be of help in prognosticating the outcome of asphyxiated babies.